Faktor-faktor yang mempengaruhi Profitabilitas: Pengaruh Perputaran Kas, Perputaran Persediaan, Perputaran Piutang - Aureta Zhabila Eka Putri; Cris Kuntadi; Rachmat Pramukty (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence profitability, namely the Effect of Cash Turnover, Inventory Turnover and Accounts Receivable Turnover, a literature study on Accounting Information Systems. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) The effect of cash turnover on profitability; 2) Inventory Turnover affects profitability and 3) Accounts Receivable Turnover affects Profitability.